La reforma laboral “de los jóvenes” en Esp aña. Esp ecial referencia a la Ley 11/2013 y el rd-ley 16/2013 - Gonzáles Díaz, Francisco A. (Revista de Derecho, 2019)
The high rate of youth unemployment in Spain, surpassing the average of the countries of the European Union, has forced a series of initiatives that were introduced in the document Entrepreneurship and Youth Employment Strategy. This article aims to approach those measures with a legal-labor component, with particular reference to Law 11/2013. This law articulates a series of measures through incentives to hiring, and its first result should lead to the reduction of youth unemployment. Therefore we need to make reference to new contractual arrangements, to the reforms of the current rules or to the recruitment incentives, which are linked to training activities.